2009
DOI: 10.1080/17408980701712148
|View full text |Cite
|
Sign up to set email alerts
|

Attributions for and consequences of student misbehavior

Abstract: Background: Effective classroom management is a critical teaching skill and a key concern of educators. As such it has been the focus of much research and as a result educators know a good deal about what happens in physical education class and the actions teachers take to deal with student behavior. Surprisingly, however, we do not know much at all about what teachers believe causes student misbehavior, nor what students say about the same issue. This seems like a critical oversight as how one explains anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 28 publications
6
45
1
3
Order By: Relevance
“…Student reports indicate that a disruptive classroom environment negatively affects learning prerequisites and outcomes throughout the educational stages (Seidman, 2005;Bru, 2009;Cothran, Kulinna & Garrahy, 2009). Addressing the issue, however, is a rather complex matter owing to the varying views among students regarding the prerequisites of the learning climate (Infantino & Little, 2005; see also Paaso, Uusiautti & Määttä, 2013 ) and the appropriateness of certain CRM policies and procedures adopted by teachers.…”
Section: Student Viewpoint On Crmmentioning
confidence: 99%
See 1 more Smart Citation
“…Student reports indicate that a disruptive classroom environment negatively affects learning prerequisites and outcomes throughout the educational stages (Seidman, 2005;Bru, 2009;Cothran, Kulinna & Garrahy, 2009). Addressing the issue, however, is a rather complex matter owing to the varying views among students regarding the prerequisites of the learning climate (Infantino & Little, 2005; see also Paaso, Uusiautti & Määttä, 2013 ) and the appropriateness of certain CRM policies and procedures adopted by teachers.…”
Section: Student Viewpoint On Crmmentioning
confidence: 99%
“…Teachers tend to attribute student misbehaviour to child and family factors (e.g., Poulou & Norwich, 2000;Mavropoulou & Padeliadu, 2002;Kulinna, 2007Kulinna, -2008, implying thus that they are not to be held accountable for student misconduct. Students, on the other hand, are more likely to attribute it to their need for attention and/or a lack of meaningful class content (Cothran et al, 2009) or to student vulnerability to pressure from other pupils, their own emotional turmoil or struggles with school work (Miller, Ferguson & Byrne, 2000). Also for students, classroom misbehaviour might be opposition to teachers' stances towards them, characterised as unfair, insensitive and negligent (Miller, Ferguson, & Byrne, 2000;Tirri & Puolimatka, 2000;Wentzel, 2002).…”
Section: Varying Views Between Students and Teachersmentioning
confidence: 99%
“…Importantly for educators, some of this research examines how these relationships are formed (Wilkins, 2006;Cothran, Kulinna, & Garragy, 2003;Ozer, Wolf, & Kong, 2008) however, there is a lack of comparative research about how positive relationships are developed differently with particular groups of students. The benefit of positive student-teacher relationships is evident for all students (Hattie, 2009;Blum, 2005;Klem & Connell, 2004;Pianta, 1999), and appears to be especially important for gifted students (GS) and students with Emotional/Behavioural Disorders (EBD).…”
Section: Introductionmentioning
confidence: 99%
“…Research on disruptive behavior in PE has traditionally focused on teachers' perceptions (e.g., Ennis, 1995;Fink & Siedentop, 1989;Placek, 1983). Cothran, Kulinna, and Garrahy (2009) recently noted that surprisingly little research has considered disruptive behavior from students' point of view in PE. Students in their study reported that disruptive behavior in many cases stemmed from a lack of motivation.…”
mentioning
confidence: 99%